The effect of calorie to protein ratio of practical diets on performance and carcass quality of broiler chickens - Tion , M.A.; Orga , M.T.; Adeka, I. A. (Nigerian Journal of Animal Production, 2021)
One hundred and ninety two sexed broiler finisher chickens were utilized in a completely randomized design to test the dietary effects of calorie: protein ratio on the performance and carcass quality of Broilers raised 10-63 days of age. Sixteen birds (8 males and 8 females) per pen and 48 per diet were Assigned at random to 12 homogenous pens, each measuring 3.5 x 1.75m? in an open sided poultry house. Feed and water were offered ad libitum. Al the end of the feeding trial, 2 birds of each sex (4 birds/pen and 12/diet), which had their weighis close to the pen average, were selected for carcass evaluation. Processed birds had their abdominal and gizzard fats recovered and weighed. Results showed that calorie: protein ratio had no significant effect on all the performance traits measured. However, statistical analysis of mean values for feed intake and feed: gain ratio was close to attaining significant level at P<0.05. Carcass traits (final body weight, fat weight, and percentage fat) were however significantly (P < 0.05) affected by calorie: protein ratio. The study gives an indication that calorie: protein ratio as wide as 178:7 can be gainfully utilized in this country for finishing broilers to market weight > 2.0kg) in 63 days.